PENGARUH EMO DEMO TERHADAP PERILAKU PENCEGAHAN STUNTING PADA IBU HAMIL - Masitah, Ravi (Universitas Cokroaminoto Palopo, 2025)
Stunting is a nutritional problem that significantly impacts the quality of human resources. The risk of stunting can occur even during pregnancy. Therefore, proper nutritional education is needed, especially for target groups like pregnant women, to prevent stunting early. Emo Demo (Emotional Demonstration) is an engaging and interactive educational method that directly involves the emotions of the target group, which can influence behavioral changes. This study aims to determine the effect of Emo Demo on stunting prevention behavior in pregnant women. A quasi-experimental design using the One Group Pretest-Posttest method was employed. The study was conducted in the working area of Puskesmas Satu Ulu, Palembang City, South Sumatra Province, in 2023. The research subjects were 30 pregnant women in the first, second, and third trimesters, selected using purposive sampling. The Wilcoxon signed ranks test results showed a change in values before and after the Emo Demo practice was given. Positive Ranks with an N value of 30 indicate that all respondents experienced an increase in pretest and posttest scores related to stunting prevention behavior. Based on the results of the study, it can be concluded that there is an effect of Emo Demo on stunting prevention behavior in the group of pregnant women with a (p-value < 0.05).